Molecular Docking of Allicin with PBP2a in MRSA: Insights into Antibacterial Mechanisms - Onche, E. P; Abdulrazak, N; Michael, E. I.; Attah, A. A (CV. Literasi Indonesia, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a significant universal public health challenge owing to its resistance to β-lactam antibiotics, mostly methicillin. Primarily, resistance is mediated through the acquisition of the mecA gene encoding penicillin-binding protein 2a (PBP2a), which diminishes the effectiveness of β-lactams. A sulfur-containing compound known as allicin, often derived from Allium sativum (garlic), has proven broad-spectrum properties of antibacteria; nevertheless, its information regarding interactions with resistance protein PBP2a and its likes remains understudied. This study made use of molecular docking analysis to examine the binding interactions between allicin and PBP2a. The binding score of allicin was -3.9 kcal/mol, which shows that allicin has a moderate affinity for the PBP2a active site when compared to vancomycin (positive control) binding energy of -15.6 kcal/mol. The interaction of allicin with key amino acids in the PBP2a catalytic site showed no hydrogen bond formation. The outcome of this research shows that allicin can serve as a potential adjunct or alternative intervention against MRSA by targeting PBP2a. The study reveals insights into allicin's mode of action and presents a basis for further research on the application of compounds derived from plants in combating antibiotic resistance.